Template-guided selection of RNA ligands using imine-based dynamic combinatorial chemistry - Juru, Aline Umuhire (Chem Commun (Camb), 2020)
This study establishes the applicability of imine-based dynamic combinatorial chemistry to discover non-covalent ligands for RNA targets. We elucidate properties underlying the reactivity of arylamines and demonstrate target-guided amplification of tight binders in an amiloride-based dynamic library.